2022
DOI: 10.1055/s-0042-1755354
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Patellofemoral Arthroplasty on Patellar Height in Patients with Patellofemoral Osteoarthritis

Abstract: Osteoarthritis (OA) in the knee is common, painful, and may be uni- or multicompartmental. The compartment affected by arthritis may be due to trauma, malalignment (varus or valgus), or in the case of patellofemoral OA, patella alta. Patellofemoral arthroplasty (PFA) is an effective partial knee replacement surgery for patellofemoral OA. We hypothesized that PFA can decrease patellar height. In addition, we predicted better outcomes for patients with patella alta before PFA and those whose patellar heights dec… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…As a result, this must be looked for preoperatively and accounted for with a surgical technique to improve patellofemoral tracking and the subsequent outcome. Similarly, patella alta and trochlear dysplasia are significantly more frequent in PFOA with an increase in both trochlear angle and Dejour score noted by Mofidi et al 47,48 . PFA can reduce patella height; however, this has not been quantified and the effect of patella height on the overall outcome of PFA is uncertain with the literature showing mixed results 44,48-50 .…”
Section: Resultsmentioning
confidence: 82%
See 1 more Smart Citation
“…As a result, this must be looked for preoperatively and accounted for with a surgical technique to improve patellofemoral tracking and the subsequent outcome. Similarly, patella alta and trochlear dysplasia are significantly more frequent in PFOA with an increase in both trochlear angle and Dejour score noted by Mofidi et al 47,48 . PFA can reduce patella height; however, this has not been quantified and the effect of patella height on the overall outcome of PFA is uncertain with the literature showing mixed results 44,48-50 .…”
Section: Resultsmentioning
confidence: 82%
“…Similarly, patella alta and trochlear dysplasia are significantly more frequent in PFOA with an increase in both trochlear angle and Dejour score noted by Mofidi et al 47,48 . PFA can reduce patella height; however, this has not been quantified and the effect of patella height on the overall outcome of PFA is uncertain with the literature showing mixed results 44,48-50 . Beckmann et al concluded that patients with patella alta are contraindicated for an inlay design based on their 2019 study showing a high rate of revision for patella clunk after PFA with the inlay HemiCAP Wave implant 51 .…”
Section: Resultsmentioning
confidence: 82%